ALS herbicide resistance mutations in Raphanus raphanistrum: Evaluation of pleiotropic effects on vegetative growth and ALS activity - Li, Mei (2013)
Background Gene mutations that endow herbicide resistance may cause pleiotropic effects on plant ecology and physiology. This paper reports on the effect of a number of known and novel target-site resistance mutations of the ALS gene (Ala-122-Tyr, Pro-197-Ser, Asp-376-Glu or Trp-574-Leu) on vegetative growth traits of the weed Raphanus raphanistrum. Results The results from a series of experiments have indicated that none of these ALS resistance mutations imposes negative pleiotropic effects on relative growth rate (RGR), photosynthesis and resource-competitive ability in R. raphanistrum plants. The absence of pleiotropic effects on plant growth occurs in spite of increased (Ala-122-Tyr, Pro-197-Ser, Asp-376-Glu) and decreased (Trp-574-Leu) extractable ALS activity. Conclusion The absence of detrimental pleiotropic effects on plant growth associated with the ALS target-site resistance mutations reported here is a contributing factor in resistance alleles being at relatively high frequencies in ALS-herbicide-unselected R. raphanistrum populations.